1992
DOI: 10.1073/pnas.89.21.10336
|View full text |Cite
|
Sign up to set email alerts
|

Quadruplex structure of d(G3T4G3) stabilized by K+ or Na+ is an asymmetric hairpin dimer.

Abstract: The ends of chromosomes contain repeats of guanine-rich sequences that can assume highly compact conformations and are presumed necessary for their biological role in chromosomal stabilization and association. We have investigated the conformational behavior of d(G3T4G3) as a function of the addition of either KCI or NaCl, in the concentration range of 50-200 mM, by using a spectrum of physical techniques and conclude that these salts induce a quadruplex species composed of two strands, each in a hairpin confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
81
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 22 publications
9
81
2
Order By: Relevance
“…To evaluate the effect of BMVC to the G-quadruplex DNA of human telomeric sequences, d(T 2 AG 3 ) 4 (Hum), we applied circular dichroism to monitor the melting temperature (Tm) of Hum quadruplexes. It has been documented that parallel fourstranded quadruplexes give a positive band f260 nm and a negative band f240 nm (27), whereas antiparallel folded quadruplexes have two positive bands around 245 and 290 nm and a negative band f265 nm (28). The 295-nm circular dichroism band was measured as a function of temperature to determine the Tm of Hum24 quadruplexes in the presence of carbazole and BMVC (29).…”
Section: Bmvc Is a Potent G-quadruplex Stabilizer And Telomerase Inhimentioning
confidence: 99%
“…To evaluate the effect of BMVC to the G-quadruplex DNA of human telomeric sequences, d(T 2 AG 3 ) 4 (Hum), we applied circular dichroism to monitor the melting temperature (Tm) of Hum quadruplexes. It has been documented that parallel fourstranded quadruplexes give a positive band f260 nm and a negative band f240 nm (27), whereas antiparallel folded quadruplexes have two positive bands around 245 and 290 nm and a negative band f265 nm (28). The 295-nm circular dichroism band was measured as a function of temperature to determine the Tm of Hum24 quadruplexes in the presence of carbazole and BMVC (29).…”
Section: Bmvc Is a Potent G-quadruplex Stabilizer And Telomerase Inhimentioning
confidence: 99%
“…NMR spectroscopy showed that each of the DNA strands self-assembled into individual bimolecular quadruplexes, with distinct topologies, in the presence of monovalent cations [21][22][23][24][25][26][27][28]. The monovalent cations are necessary to coordinate in the core of the quaduplexes and so to stabilize the structures.…”
mentioning
confidence: 99%
“…The monovalent cations are necessary to coordinate in the core of the quaduplexes and so to stabilize the structures. [Note: Subsequently in this paper, the sequences will be described as d( 2 by the absence of a middle G-quartet (Figure 1d), so that the guanine bases are arranged 5=-syn-synanti-loop-syn-anti-anti-3= in one strand and 5=-syn-antianti-loop-syn-syn-anti-3= in the other [23][24][25][26]. In contrast, the structure of the bimolecular [d(G 3 G 4 )] 2 is special (Figure 1c), in that one guanine residue leaps over the middle G-quartet, turning an antiparallel strand parallel to its own half, and so that two dangling guanines reside at opposite ends of the quadruplex [27,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the sequence d(G 3 T 4 G 3 ) forms a two-stranded quadruplex in the presence of excess amounts of either Na þ or K þ . [33][34][35] In contrast to the unimolecular quadruplexes, addition of near stoichiometric amounts of Ba 2þ , for example, results in virtually no quadruplex formation, as illustrated in Figure 2. However, if methanol is present, then a peak near 300 nm, indicative of antiparallel quadruplex formation, appears.…”
Section: Cosolvents Do Not Affect Quadruplex Structurementioning
confidence: 99%